2015
DOI: 10.1016/j.ejbt.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative proteomic study of white and black glutinous rice leaves

Abstract: Background: Black glutinous rice contains remarkable levels of anthocyanins, which possess anti-oxidative properties and thus have health benefits. The accumulation of anthocyanins in grains of thirty black glutinous rice varieties was measured, and the results revealed that the accumulated anthocyanin content ranged from 0.262 to 2.539 mg/g. Black glutinous rice Br no. 19 was selected, and its leaf protein expression profile was compared with that of white glutinous rice RD 6 using 2D-PAGE, and the protein sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Likewise, the majority of the genetic variation being within regions rather than between regions was reported in the traditional Philippine pigmented rice, and 589 pigmented rice accessions occur as both indica and japonica types [53]. In Northeastern Thailand, the total anthocyanin concentration of 30 local glutinous purple rice accessions ranged from 26 to 254 mg/100 g [54]. The latter study also evaluated total anthocyanin concentration among Anthocyanin occurrence in the grain is very divergent, since most purple rice varieties are traditional/local rice that reflect differences among regions and growing environments (glutinous and non-glutinous rice types and upland and lowland rice types) [51,52].…”
Section: Variation In Grain Anthocyaninmentioning
confidence: 99%
“…Likewise, the majority of the genetic variation being within regions rather than between regions was reported in the traditional Philippine pigmented rice, and 589 pigmented rice accessions occur as both indica and japonica types [53]. In Northeastern Thailand, the total anthocyanin concentration of 30 local glutinous purple rice accessions ranged from 26 to 254 mg/100 g [54]. The latter study also evaluated total anthocyanin concentration among Anthocyanin occurrence in the grain is very divergent, since most purple rice varieties are traditional/local rice that reflect differences among regions and growing environments (glutinous and non-glutinous rice types and upland and lowland rice types) [51,52].…”
Section: Variation In Grain Anthocyaninmentioning
confidence: 99%
“…To date, there is limited information on the diversity of leaf color in rice crops, including light green, dark green, purple and pink colors, detected by RGB cameras via high-throughput phenotyping in relation to plant canopy estimation and color segmentation as an alternative information source (Peng et al, 2006;Chin et al, 2016;Khan et al, 2020). Riceberry is a previously documented indica rice variety with a purple leaf sheath (anthocyanin enrichment in the leaf sheath, panicle and pericarp of rice grain) (Daiponmak et al, 2010;Phonsakhan and Kong-Ngern, 2015). Additionally, in the current study rice varieties with light green, green and dark green leaves and short-day photoperiod insensitivity were selected-Homchonlasit, IR64, PT1, RD41, and RD43-as well as a semidwarf rice with a high-yield genotype, IR64, for validation (Mackill and Khush, 2018;Pongprayoon et al, 2019;Tisarum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Maksup and others (Maksup et al, 2017) compared the proteomic profile of germinated and non-germinated brown rice, in which germinated brown rice exhibited higher protein expression than nongerminated brown rice. A previous study reported that at least six proteins related to anthocyanins were expressed in black and not white glutinous rice leaves (Phonsakhan & Kong-Ngern, 2015). Using sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) with Coomassie Brilliant Blue (CBB) staining, Sari and others (Sari et al, 2019b) detected specific protein bands in black rice seeds from Java, while those proteins were not detected in white or red rice.…”
Section: Introductionmentioning
confidence: 99%